Methylation‐specific multiplex ligation‐dependent probe amplification: utility for prenatal diagnosis of parental origin in human triploidy. (23rd August 2013) - Joergensen, M. W.; Rasmussen, A. A.; Niemann, I.; Hindkjaer, J.; Agerholm, I.; Bolund, L.; Kolvraa, S.; Sunde, L.
ABSTRACT Objective When a triploid pregnancy is diagnosed prenatally, gynaecologists have traditionally relied on the histopathological examination of the tissue from the terminated pregnancy to determine if the pregnancy is molar. However, reproducibility is poor and variability is high when diagnosing hydatidiform moles. Triploid pregnancies can have either the chromosomal constitution of two maternal and one paternal set, or two paternal and one maternal set, but only the conceptuses with two paternal sets have the potential to cause maternal complications. Therefore, it would be beneficial to introduce a method that gives the gynaecologist the parental origin of the genome of the triploid conceptus as early as possible, without delaying the process by first collecting parental samples. Methods Using methylation‐specific multiplex ligation‐dependent probe amplification, we measured methylation levels at different imprinted sites. Results We were able to correctly determine the parental origin of the genome in all 105 triploid pregnancies analysed. Conclusions We present methylation‐specific multiplex ligation‐dependent probe amplification as a method capable of determining the parental origin of the genome of triploid conceptuses within 24 h; it is inexpensive, simple and easy to use, and parental samples are not needed. © 2013 John Wiley & Sons, Ltd.